THE FACTORS ASSOCIATED WITH OBESITY IN PT BUKIT MURIA JAYA KARAWANG OFFICE DIVISION EMPLOYEES - Adhiraga, Winda Bola Adhiraga; Wahidin, Mugi; Heryana, Ade; Yusvita, Fierdania (Indonesia Epidemiological Journal, 2024)
Background: Obesity is one of the health problems that often occur in employees who do not maintain a healthy lifestyle. This study aims to determine the factors associated with obesity in employees of the office division of PT BMJ Karawang in 2023 Methods: This study used a quantitative approach with a cross-sectional study research design. The study will be conducted from August 2023 to September 2023. The population in this study was 190 workers and the sample used was 83 respondents with a simple random sampling technique. The variables studied were age, sex, food intake, and physical activity. Data collection was carried out using questionnaires, and secondary data from the 2022 MCU results and employee data of PT Bukit Muria Jaya Karawang. Results: The data will be analyzed with a chi-square test with results showing that there is asignificant relationship between nutritional adequacy (p-value = 0.000) and physical activity (p-value = 0.000) with obesity. While the variables that did not have a significant relationship were gender (p-value = 0.906), age (0.185). Conclusion: Efforts are needed to control obesity through healthy eating patterns and increasing physical activity in employees.